The Health Benefits of Fruits and Vegetables - Del Río Celestino, Mercedes; Villa, Rafael Font (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue gathers 14 original research papers to disseminate new data on phytochemicals from vegetables and fruits, which are recommended for their health-promoting properties. Epidemiological, toxicological and nutritional studies suggest an association between fruit and vegetable consumption and lower incidence of chronic diseases, such as coronary heart problems, cancer, diabetes, and Alzheimer's disease. In this Special Issue the following topics have been addressed: (i) the protective roles, antioxidant and others bioactivities such as genotoxic and antigenotoxic effects in the Drosophila melanogaster animal genetic model and pro-apoptotic capacities against cancer processes, including cytotoxicity and clastogenic DNA activity, using an in vitro human cancer model (HL-60 cell line, (ii), new sustainable approaches based on near-infrared spectroscopy to determine the quality, (iii) broad-scale metabolomic investigation for the development of functional food and, (iv) processing techniques that can modify the initial nutritional and antioxidant content of fruits, vegetables, and additives. In summary, the information in this Special Issue will be interesting for researchers in this field and the general public interested in the relationship between vegetables and health.